Shell-model studies in mass 10 to 15 nuclei : an evaluation of the modified surface delta two-nucleon interaction - Richter, Werner August (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1978.